MANAJEMEN PROGRAM PENDIDIKAN KARAKTER DALAM MENINGKATKAN SIKAP SOSIAL SISWA DI ERA DISRUPSI INFORMASI - Ula, Hamidatul; suwarno, suwarno; Suradji, Muchamad; M̤ṳk̤h̤l̤a̤s̤, M̤ṳk̤h̤l̤a̤s̤ (TA'LIM : Jurnal Studi Pendidikan Islam, 2024)
The challenge of education in Indonesia in the era of information disruption is currently faced with the problem of declining student social attitudes. Strengthening character education has not yet become the value of Indonesian character and culture according to Pancasila. Like there are still many cases where students are indifferent and individualistic. They don't have social sensitivity, one example is when someone gets into a disaster, instead of being helped, they take a photo, make a video of it, and send it to social media. Therefore, education in Indonesia must be able to equip students with a good social character. This study aims to find out in-depth and describe the implementation of character education program management to improve students' social attitudes in facing the era of information disruption. This research is descriptive qualitative research using a phenomenological approach with the type of field research (Field Research). The research was conducted at Madrasah Aliyah Negeri (MAN) 6 Jombnag. The method of determining respondents is done with a purposive system. While the data collection technique uses four techniques, namely documentation, observation, interviews, and combination/triangulation. Interactive model data analysis technique with four stages, namely 1) data collection, 2) data condensation, 3) data display, and 4) conclusion drawing/verifying. The results showed that the implementation of character education program management to improve students' social attitudes in facing the era of disruption was carried out through four stages, namely planning, organizing, and implementing. and supervision. The planning, organizing, and implementation stages have been carried out by the management function. While at the monitoring stage, it has not been carried out properly. Program evaluation and accountability of program implementers have not been carried out, so they do not know which ones need to be improved and which ones need to be improved. The findings of this study are still limited to character education management programs, so further research is needed related to the effectiveness of character education programs in improving students' social attitudes at MAN 6 Jombang.